1970
DOI: 10.1111/j.1365-246x.1970.tb06089.x
|View full text |Cite
|
Sign up to set email alerts
|

The Implications of Terrestrial Heat Flow Observations on Current Tectonic and Geochemical Models of the Crust and Upper Mantle of the Earth

Abstract: The average heat flow through continental orogenic belts decreases with the age of the orogeny to an approximately constant value for the Precambrian shields and platforms. The average heat flow for provinces of the North Pacific decreases with the age of the province. The mean heat flow through the province younger than 10 million years is 2.82 p cal * The best estimate of the standard error of the mean of a small sample is given by the law of Studat-Fisher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
249
1
2

Year Published

1973
1973
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 707 publications
(262 citation statements)
references
References 33 publications
10
249
1
2
Order By: Relevance
“…In the plate model, the temperature is assumed to be held fixed by some mechanism at a depth on the order of 100 km (1,3,4). The models are quite similar near the ridge crest before cooling has penetrated very deep, but over the ocean b€sins, the models differ substantially.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the plate model, the temperature is assumed to be held fixed by some mechanism at a depth on the order of 100 km (1,3,4). The models are quite similar near the ridge crest before cooling has penetrated very deep, but over the ocean b€sins, the models differ substantially.…”
Section: Introductionmentioning
confidence: 94%
“…One of the more striking successes of the kinematic model of plate tectonics is that the variation in oceanic depth away from ridges can be understood in terms of simple models of cooling of the lithosphere (1)(2)(3)(4)(5). Oceanic heat flow can be explained by these models if hydrothermal activity at the ridge is taken into account (6); recently it has been demonstrated that the short wavelength change in geoid elevation over ridges predicted by these simple models is also readily observed (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Appendix 2 However, most of the observations to date measure only the near-surface effects of the elevated mantle temperatures, such as high heat flow (Lee and Uyeda, 1965;Sclater and Francheteau, 1970) or unusually low P and S velocities n n (Talwani, et al, 1965;Keen and Tramontini, 1970;Hart and Press, 1972). Other techniques measure a total effect averaged over a vertical section of the upper mantle.…”
Section: Figure Al 238mentioning
confidence: 99%
“…The mid-ocean ridge system is thought to be essentially in isostatic equilibrium (Sclater and Francheteau, 1970), thus I require constant mass in a column above a compensation depth of 100 km.…”
Section: 2mentioning
confidence: 99%
“…The major difference of our study from the previous studies is that we estimate the slab pull and ridge push forces as definitely as possible, before solving the equilibrium equations. Since the thermal structure of oceanic lithospheres has been well explained in some models (e.g., PARKER and OLDENBURG, 1973 ;SCLATER and FRANCHETEAU, 1970), we can calculate the ridge push force, which may be the force arising from density variations in cooling oceanic lithospheres. The slab pull force resulting from the density contrast between the slab going down from the trench and the surrounding mantle is also calculated in advance.…”
Section: Introductionmentioning
confidence: 99%